IMPLEMENTAÇÃO DE SISTEMAS DE GESTÃO INTEGRADA: ESTUDO DE CASO DE UM GASODUTO - Oliveira, Ivanildo de (2007)
This dissertation approaches the Integration Management Systems of QHSE in the organizations and it presents a Case Study on the implementation of the Integrated Management System of a gas pipeline of Petróleo Brasileiro S/A (PETROBRAS) company. The main focus of the study is the search of knowledge on the main ad-vantages and disadvantages that interfere in the implementation of the integration of the systems. The Quality, allied to the Environment Occupational Health and the em-ployees' Safety in the organizations are certified through the ISO standards of the families 9000 and 14000 and for the OHSAS 18001 standard, which draw the roads to be trodden by the interested parties in the integration of the Management Sys-tems. With the growing pressure in the companies to do more with minus, several of them they are seeing the integration of the Management Systems as an excellent opportunity to reduce costs with the development and maintenance of separate sys-tems, or of countless programs and actions that, most of the time, if they put upon and they cut unnecessary expenses. The study shows that it is costly to any com-pany to maintain two or three systems at the same time without integration. The maintenance cost is elevated, there are damages in a general way and the results are not satisfactory, in case they are not integrated in a single system. It is possible to observe that indeed an Integrated Management System in a production or service company brings more advantages, putting company to compete in a global market.